Differential risk of severe infection in febrile neutropenia among children with blood cancer or solid tumor. Issue 2 (August 2019) - Delebarre, Mathilde; Dessein, Rodrigue; Lagrée, Marion; Mazingue, Françoise; Sudour-Bonnange, Hélène; Martinot, Alain; Dubos, François
Abstract: Objective: To describe and analyze the differences between infections in children with febrile neutropenia (FN) treated for solid tumor or blood cancer. Methods: A prospective study included all episodes of FN in children from April 2007 to April 2016 in 2-pediatric cancer centers in France. Medical history, clinical and laboratory data available at admission and final microbiological data were collected. The proportion of FN, severe infection, categories of microorganisms and outcomes were compared between the two groups. The presumed gateway of the infection was a posteriori considered and evaluated. Results: We analyzed 1197 FN episodes (mean age: 8 years). 66% of the FN episodes occurred in children with blood cancer. Severe infections were identified in 23.4% of episodes overall. The rate of severe infection (28.4% vs. 10.4%), types of microorganisms and the need for a management in intensive care unit (2.6% vs. 0.5%) was significantly different between children with blood cancer and solid tumor. Digestive or respiratory presumed gateway of the infections was less frequent for patients with solid tumor. Conclusion: Given these important microbiological and clinical differences, it may be appropriate to consider differently the risk of severe infection in these two populations and therefore the management of FN.